Examining the multiple impacts of technological progress on CO2 emissions in China: A panel quantile regression approach - Wang, Shaojian; Zeng, Jingyuan; Liu, Xiaoping (Renewable & sustainable energy reviews, 2019)
Whilst a plethora of literature has viewed technological progress as one of the critical influencing factors in relation to energy consumption and CO2 emissions, little effort has been made to identify the sectoral differences in the relationship between technological progress and CO2 emissions. Thereby, this paper remedies the inadequacies in the extant literature by empirically investigating the impact of technological progress on CO2 emissions, specifically taking into account its heterogeneous effect in various economic sectors. This paper first decomposes the effect of technological progress as taking place in heavy industry, in light industry, in construction industry, and in service industry. A panel quantile regression approach and a balanced city panel data model are then applied, covering the period 2001–2013 in China. The empirical results show that technological progress in heavy industry and light industry surprisingly facilitates a higher level of CO2 emissions, despite its prominent contribution to energy efficiency improvement. Meanwhile, as distinct from the effect it shows in the heavy and light industries, technological progress in construction and service industries exerts a negative effect on CO2 emissions. Additionally, this paper further discovers that the strength of the multiple impacts of technological progress also varies with the level of emitters. By studying the heterogeneous effect brought about by technological progress in different economic sectors and emitters, this paper provides a comprehensive understanding of the relationship between CO2 emissions and technological progress. •The study considers the sectoral and scale heterogeneity of technological progress in relation to CO2 emissions.•We apply a panel quantile regression approach to balanced city-level panel data.•Technological progress within different economic sectors exerts different effects on CO2 emissions.•The role of technological progress in moderating energy intensity varies across emitters.